2022
DOI: 10.1155/2022/9962421
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effects of Acupuncture for Stroke Patients Recovery

Abstract: Stroke is assumed as one of the common cerebrovascular diseases that endangers human health and life. Its incidence and mortality rates are high, while survivors (50% to 70%) suffer from different degrees of disability. Hemiplegia is a common disability after stroke, mainly manifested as muscle weakness of the affected side, limb spasm, and limited activity, which severely impacts a patient’s daily life. There are various rehabilitation methods for stroke hemiplegia, including modern rehabilitation medicine, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…R language is an effective data mining tool that offers open-source, free, comprehensive, and user-friendly features. It integrates statistical analysis and graphic display and can analyze the law of acupoint selection, as well as the clinical effects of acupuncture on patient recovery [53] . R provides powerful statistical tools, visualization capabilities, and machine-learning algorithms that can help identify patterns and provide insights from acupoint selection data.…”
Section: Data-driven Acupuncture Prescription: From Evidence To Practicementioning
confidence: 99%
“…R language is an effective data mining tool that offers open-source, free, comprehensive, and user-friendly features. It integrates statistical analysis and graphic display and can analyze the law of acupoint selection, as well as the clinical effects of acupuncture on patient recovery [53] . R provides powerful statistical tools, visualization capabilities, and machine-learning algorithms that can help identify patterns and provide insights from acupoint selection data.…”
Section: Data-driven Acupuncture Prescription: From Evidence To Practicementioning
confidence: 99%
“…Acupuncture is recommended by the WHO as a complementary therapy for post-stroke rehabilitation (Chavez et al, 2017). Research has shown that acupuncture can enhance muscle strength, muscle tone, and balance function in stroke patients (Fan et al, 2020;Guo and Cheng, 2022;Zhang et al, 2022). Therefore, it is widely utilized as a beneficial intervention to improve motor dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%